Surgical treatment methods in the course of psychiatric disorders: Deep brain stimulation—Novel insights and indications - Ugo Giordano; Jakub Mizera; Elżbieta Żak; Justyna Pilch; Paulina Tomecka; Tomasz Dudzik; Mikołaj Palczewski; Weronika Biziorek; Patryk Piotrowski (Indian Journal of Psychiatry)
Deep brain stimulation (DBS) is a relatively dated treatment procedure that emerged in the late 1980s. Nonetheless, numerous studies are being carried out to examine its influence on the human brain and develop new treatment indications. This systematic review aims to summarize the current state of knowledge referring to DBS, investigate novel insights into its indications, and discuss the technical aspects and rationale behind DBS application. In particular, we sought to subject to scrutiny the application of DBS specifically in anorexia nervosa (AN), various addiction types, depression, and obsessive–compulsive disorders (OCDs). The method is supposed to offer promising results, especially in pharmacologically resistant forms of the upper-mentioned psychiatric disorders. Moreover, further insight has been provided into the historical notions of the method and differences in the surgical approach in specific disease entities. Furthermore, we mark the possible influence of comorbidities on treatment results. Our review consists of articles and studies found on PubMed, Google Scholar, Cochrane, and Scopus, which were then analyzed with scrutiny in the identification process, including the most resourceful ones. After methodological quality and risk of bias assessment, a total of 53 studies were included. To this date, DBS’s usefulness in the treatment of AN, OCDs, depression, and addictions has been proven, despite an ongoing debate concerning the technical aspects and parameters when applying DBS. To the best of our knowledge, we have not found any paper that would recapitulate the current state of DBS in the context of psychiatric disorders with an addition of technical insights.